2011
DOI: 10.3892/ijo.2011.903
|View full text |Cite
|
Sign up to set email alerts
|

Flexible hysteroscopy with narrow band imaging (NBI) for endoscopic diagnosis of malignant endometrial lesions

Abstract: Abstract. Narrow band imaging (NBI) for detection of blood vessels and microstructures on the mucosal surface is used in gastrointestinal endoscopy since it can improve qualitative diagnosis and detection of lesion. However, there are no studies on flexible hysteroscopy using NBI. We performed flexible hysteroscopy with NBI for outpatients to investigate the sensitivity and specificity of endoscopic diagnosis of malignant endometrial lesions. Of patients who attended our hospital for suspected lesions in the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Increased sensitivity of NBI vs. WL for the detection of atypical endometrial hyperplasia - high-risk hyperplasia (HRH) was reported in five studies ( 10 , 20-23 ). The reported sensitivity of NBI vs. WL for HRH was 60 vs. 20%, P<0.005( 36 ), 78.38 vs. 64.86%, P<0.005( 20 ), 78.6 vs. 63.7%, P<0.001( 23 ), 93.5 vs. 82.6%, P=0.006( 24 ) and 97.2 vs. 82.6%, P<0.005( 21 ).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Increased sensitivity of NBI vs. WL for the detection of atypical endometrial hyperplasia - high-risk hyperplasia (HRH) was reported in five studies ( 10 , 20-23 ). The reported sensitivity of NBI vs. WL for HRH was 60 vs. 20%, P<0.005( 36 ), 78.38 vs. 64.86%, P<0.005( 20 ), 78.6 vs. 63.7%, P<0.001( 23 ), 93.5 vs. 82.6%, P=0.006( 24 ) and 97.2 vs. 82.6%, P<0.005( 21 ).…”
Section: Resultsmentioning
confidence: 95%
“…2 . The years with the highest frequency of publications were 2010 and 2011 with 5 studies produced each year and the country which produced the highest number of studies was Japan with 11 studies ( 13 , 18 , 21 , 22 , 28 , 31-33 , 35 ), followed by Italy with 8 studies ( 9 , 10 , 15-17 , 19 , 20 , 36 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical excision remains one of the most effective methods for gynecomastia management, particularly in patients with fibrosis or with a disease course of >1 year ( 7 ). Previously, minimally invasive techniques, including power-assisted and ultrasound-assisted liposuction, have been a popular approach due to their satisfactory cosmetic outcome ( 12 15 ). However, interest is now focused on minimally invasive surgery to minimize external scars ( 14 ).…”
Section: Discussionmentioning
confidence: 99%